Effects of neighbourhood and household sanitation conditions on diarrhea morbidity: Systematic review and meta-analysis. - Youngmee Tiffany Jung; Ryan James Hum; Wendy Lou; Yu-Ling Cheng (PLoS ONE, 2017)
Sanitation in neighbourhood and household domains can provide primary protection against diarrhea morbidity, yet their distinct health benefits have not been succinctly distinguished and reviewed. We present here the first systematic review and meta-analysis of the distinct effect of neighbourhood and household sanitation conditions on diarrhea morbidity. We identified studies reporting the effect of neighbourhood-level exposure to wastewater or household sanitation facilities on diarrhea, by performing comprehensive search on five databases, namely the Cochrane library, PubMed, Embase, Scopus and Web of Science, from the earliest date available to February 2015. Twenty-one non-randomized studies and one randomized controlled trial met the pre-determined inclusion criteria, consisting of six datasets on neighbourhood sanitation conditions (total 8271 subjects) and 20 datasets on household sanitation (total 20021 subjects). We calculated the pooled effect estimates of neighbourhood and household sanitation conditions on diarrhea morbidity using the inverse variance random-effects model. The pooled effect estimates showed that both neighbourhood sanitation conditions (odds ratio = 0.56, 95%CI: 0.40-0.79) and household sanitation (odds ratio = 0.64, 95%CI: 0.55-0.75) are associated with reduced diarrheal illness, and that the magnitudes of the associations are comparable. Evidence of risk of bias and heterogeneity were found in the included studies. Our findings confirm that both neighbourhood sanitation conditions and household sanitation are associated with considerable reduction in diarrhea morbidity, in spite of a number of methodological shortcomings in the included studies. Furthermore, we find evidence that neighbourhood sanitation conditions is associated with similar magnitude of reduction in diarrhea morbidity as household sanitation. The findings suggest that, in addition to household sanitation provision, dual emphasis on neighbourhood sanitation through public sanitation infrastructure provision and community-wide sanitation adoption is advisable for effective reduction of diarrheal disease burden.